Propriedades estruturais, ópticas e espectroscópicas de vidros Cálcio Boroaluminato dopados com Eu3+/Eu2+ - GOMES, Bernardo Rurik Aparecido (2018)
This work describes the synthesis and characterization of europium rare-earth doped calcium boroaluminate (CaBAl) glasses with carbon varying to control the ratio of Eu2+ and Eu3+ during the melting process, aiming to understand how the coexistence of these valences changes the structural, optical and spectroscopic properties of this material. The samples with composition of 23CaO - 50B2O3 - 15Al2O3 - 10CaF2 - 2Eu2O3 and carbon concentration added from 2,75; 5 and 7,5 wt%, have been prepared by using melt-quenching method in air atmosphere. The X-ray diffraction results confirmed the amorphous nature of the glasses studied. The Fourier Transform Infrared Spectroscopy results showed that the glass is formed by BO3 and BO4 structures, and that the addition of carbon did not change the number of non- bridging oxygen. The volumetric density, molar volume, refractive index and electronic polarizability values have not changed, indicating that the addition of carbon did not modify the structure of the glasses. Absorption spectra exhibited five Eu3+ characteristic bands and one band attributed to Eu2+ for the samples with carbon, indicating the coexistence of these two valences in the glass. The excitation spectra showed a maximum intensity at 398 nm for Eu3+ and a band at 250-400 nm for Eu2+. The luminescence spectra, obtained under excitation at 307, 314, 323, 346, 380 and 395 nm, showed that the x and y coordinates of the CIE chromaticity diagram red-shifted as the excitation wavelength increased. The intensity of bivalent europium emission spectra, upon 405 nm excitation, increased with carbon content. CIE chromaticity coordinates were calculated to evaluate the white light emission as a function of increase Eu2+ concentration. The CRI value for the sample synthesized with 5% carbon was 81, higher than values found in the literature for RGB white LEDs and neodymium incandescent lamps. All results indicate that these glasses have potential for applications in White Light Emitting Diodes.